Osteogenic Enhancement Between Icariin and Bone Morphogenetic Protein 2: A Potential Osteogenic Compound for Bone Tissue Engineering - Zhang, Xin; Lin, Xingnan; Liu, Tie; Deng, Liquan; Huang, Yuanliang; Liu, Yuelian (Frontiers in Pharmacology, 2019)
Icaiin, a typical flaonol glycoside, is the main active component of Herba Epimedii, which was used to cure bone related diseases in China for centuries. It has been reported that Icariin can be delivered locally by biomaterials and it has an osteogenic potential for bone tissue engineering. Biomimetic calcium phosphate bone substitute (BioCaP) is a novel drug delivery system. Our study aimed to evaluate its osteogenic potential when Icariin was internally incorporated into the BioCaP granules. The BioCaP combined with Icariin and bone morphogenetic protein 2 (BMP-2) was investigated in vitro using a MC3T3-E1 cell line as well as to repair 8 mm diameter critical size bone defects in the skull of SD male rats. BioCaP was fabricated according to a well established biomimetic mineralization process. In vitro, the effects of BioCaP alone or BioCaP with Icariin and/or BMP-2 on cell proliferation and osteogenic differentiation of MC3T3-E1 cells were systematically evaluated. In vivo, BioCaP alone or BioCaP with Icariin and/or BMP-2 were established to study the bone formation in a critical sized bone defect created in a rat skull. Samples were withdrawn for Micro-CT and histological analysis after twelve weeks. The results indicated that BioCaP incorporated with or without Icariin had a positive effect on the osteogenic differentiation of MC3T3-E1. BioCaP with Icariin can have better osteogenic efficiency. But they had no influence on cell proliferation. The addition of Icariin had better osteogenic potential than BioCaP with BMP-2 alone. The protein and mRNA expression of ALP and OCN and mineralization were better as well. In vivo, the volume of newly formed bone resulting BioCaP incorporate internally with both Icariin and BMP-2 was significantly higher than the control group and BioCaP with either Icariin or BMP-2. BioCaP with Icariin induced more new bone formation than did BioCaP alone. Micro-CT analysis revealed that the bone mineral density of newly formed bone resulting from BioCaP with Icariin alone /or with BMP-2 alone has no significant difference. Therefore, synergistic osteogenesis of Icariin and BMP-2 was helpful for bone tissue engineering.